A THOROUGH STUDY ON A CHILD LEARNING HER FIRST LANGUAGE: A Case Study on a Three-Year Old Child - Suwandi Suwandi (Universitas PGRI Semarang, 2010)
Abstract ?é?á This paper discusses mainly on?é?á the development of the language acquisition of the three year old child. The object of the study happens to be the writer?óÔé¼Ôäós granddaughter. So he could observe her totally, day by day for three years to see how her?é?á language acquisition developed. He recorded the produced sounds, words and sentences whether they are meaningful or not in order to see how she finally could form?é?á meaningful utterances. The fact that learning a first language needs much energy, time and endless effort; since she was?é?á a baby, the environment (the parents, grandparents, aunts etc) has been trying to stimulate her to talk. The response is astounding; she seems to understand what the adults have been communicating. Gradually, when she is three years old she can produce meaningful words, or utterances that can be understood by the adults and even can be used for communication. ?é?áTherefore, in this paper, the writer will reveal the process of how a child learns her mother tongue and show the progress of the language acquisition starting from the first cry until the ability to produce meaningful utterances. ?é?á